2011
DOI: 10.1007/978-3-642-22362-4_11
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Rating Scales on User’s Rating Behavior

Abstract: As showed in a previous work, different users show different preferences with respect to the rating scales to use for evaluating items in recommender systems. Thus in order to promote users' participation and satisfaction with recommender systems, we propose to allow users to choose the rating scales to use. Thus, recommender systems should be able to deal with ratings coming from heterogeneous scales in order to produce correct recommendations. In this paper we present two user studies that investigate the ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 9 publications
(15 reference statements)
3
20
0
Order By: Relevance
“…Explicit feedback recommenders let users rate items, (e.g. youtube.com, see also McNee et al 2002;Cena et al 2010;Gena et al 2011), critique items (see also Chen and Pu 2012;Viappiani et al 2006), assign weights to item attributes (see also Häubl et al 2004), or indicate their specific needs (e.g. HP.com 'help me choose', see also Felix et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Explicit feedback recommenders let users rate items, (e.g. youtube.com, see also McNee et al 2002;Cena et al 2010;Gena et al 2011), critique items (see also Chen and Pu 2012;Viappiani et al 2006), assign weights to item attributes (see also Häubl et al 2004), or indicate their specific needs (e.g. HP.com 'help me choose', see also Felix et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the ability to watch the trailer of a movie, users can not watch movies on the IMDb site before rating them, something possible in a system like Netflix. Moreover, the rating scale may also affect the users [Gena et al 2011], since the IMDb platform allows to rate movies using a 10-star feedback system, instead of the more common 5-star feedback system (like MovieLens).…”
Section: External Validitymentioning
confidence: 99%
“…Aiming at defining a general model of rating scales, we examined thirteen rating scales described by van Barneveld & van Setten (2004), Gena et al (2011) and Nobarany et al (2012): 3-, 5-and 10-point stars, bare numbers, smileys, sliders ranging -10/+10, -1/+1 and 0/10, likert-like scales ranging -10/+10 and 1/5 and 1-, 2-, and 3-point thumbs (see Figure 1). First, we identified a list of features which could be used to describe them, based on the literature and our insights, and we organized it in a model (Section 2.1).…”
Section: A Model Of Rating Scalesmentioning
confidence: 99%
“…Finally, Gena et al (Cena et al, 2010;Gena et al, 2011) adopted a different perspective, studying the influence of rating scales on user ratings. They introduced the concept of "rating scale personality" (resulting from user perception of a scale), and showed that it can influence …”
Section: Yesmentioning
confidence: 99%
See 1 more Smart Citation